The presence and variant allele fraction of EGFR mutations in ctDNA and development of resistance. (May 2019) - O'Kane, Grainne M.; Liu, Geoffrey; Stockley, Tracy L.; Shabir, Muqdas; Zhang, Tong; Law, Jennifer H.; Le, Lisa W.; Sacher, Adrian; Shepherd, Frances A.; Bradbury, Penelope A.; Leighl, Natasha B.
Highlights: Multi-gene NGS panels can be used to detect mutations and the %VAF in liquid biopsies. The presence of EGFR mutations in ctDNA may predict a shorter progression free survival interval. A high % variant allele fraction of mutations may indicate progressive disease. Abstract: Background: Peripheral blood sampling for detection of EGFR T790M in cell-free circulating tumour (ct) DNA in TKI-resistant EGFR mutant ( EGFR m) lung cancer is now standard. The value of more comprehensive sequencing is unknown. Methods: Prospective ctDNA analysis in patients with EGFR m NSCLC was performed using a next generation sequencing (NGS) panel of regions of 11 genes detecting single nucleotide variants and small insertions/deletions at ≥0.1% variant allele frequency (VAF) was performed. Patients were grouped according to treatment phase, including: (A) pre EGFR-TKI, (B) stable or responding to EGFR-TKI, (C) radiographic progression during EGFR-TKI, and (D) during chemotherapy treatment. Results: Seventy-two patients with stage IV EGFR m NSCLC were enrolled and first blood samples were analysed. Primary sensitizing mutations in del19 or L858R were present in 66 (92%) and uncommon EGFR m in 6 (8%). Mutations in ctDNA were found in 53 samples (74%). T790M was detected in 3 of 4 patients with T790M-negative tissue. Other co-occurring EGFR m were found in 10 patients (7%) including K745R during first-line osimertinib. TP53 (n = 10), KRAS (n = 1), PI3KCA (n = 1) and ALK (n = 3) gene mutations also were detected. The presence of an EGFR m (excluding T790M) was associated with untreated or progressive disease, p = 0.04. In TKI-treated patients without radiologic progression, median progression free survival (PFS) was 10 months versus 2.1 months (HR 2.22, 95% CI: 0.89–5.54, p = 0.08) if an EGFR m in ctDNA was detected. If T790M was present in ctDNA, median PFS was 3.0 months versus 9.7 months (HR 4.59, 95% CI: 1.43–14.73, p = 0.005). High % VAF of both EGFR m and T790M correlated with inferior PFS (p = 0.01 and p = 0.03 respectively). Conclusion: In addition to the emergence of resistance mutations, the presence of the primary or co-occurring EGFR m in patients receiving EGFR-TKIs may associate with shorter PFS and may be useful in longitudinal analyses of ctDNA to direct therapy.